2023
DOI: 10.3390/curroncol30020187
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Patients with Metastatic Renal Cell Carcinoma

Abstract: Background: Metastatic renal cell carcinoma (mRCC) is an aggressive cancer characterised by an increased recurrence rate and an inadequate response to treatment. This study aimed to investigate the importance of the neutrophil-to-lymphocyte ratio (NLR) as a prognostic marker for long-term survival in patients with mRCC. Methods: We retrospectively analysed data from 74 patients with mRCC treated at our medical centre with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs). We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Specifically, greater NLR correlates with worse outcomes in both non-metastatic and metastatic RCC. 11,12,[20][21][22] While most of these studies do not focus on RCC with a tumor thrombus, two recent papers have. Nagamoto et al 11 looked at patients with RCC and an IVC thrombus and concluded that a NLR ⩾ 2.9 was an independent predictor of poor 5-year cancer-specific survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, greater NLR correlates with worse outcomes in both non-metastatic and metastatic RCC. 11,12,[20][21][22] While most of these studies do not focus on RCC with a tumor thrombus, two recent papers have. Nagamoto et al 11 looked at patients with RCC and an IVC thrombus and concluded that a NLR ⩾ 2.9 was an independent predictor of poor 5-year cancer-specific survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The normal range of NLR in healthy adults varies between 1 and 3. Values higher than three are considered pathological [47][48][49][50]. Therefore, it is essential to find a cut-off value to mark the lower and the upper limit of NLR associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Large multi-center studies are needed to confirm these findings. These years, some systemic inflammatory and immune response indicators such as C-reactive protein and neutrophil to lymphocyte ratio (NLR) were considered to predict prognosis ( 32 ). Our nomogram included preoperative neutrophils, which was one of independent risk factor of OS.…”
Section: Discussionmentioning
confidence: 99%